International Students’ Motivations and Decisions to do a PhD in Canada: Proposing a Three-Layer Push-Pull Framework - Zhang, You; O'Shea, Michael; Mou, Leping (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
The study aims to explore which factors influence international students’ decision to pursue doctoral studies in Canada. Drawing on the push-pull model and the mechanism of educational decision making, this study uses semi-structured interviews to gather data and explores themes such as political and economic forces, institutional factors, social background and experience, and individual motivation in students’ decision making. Our study identifies multiple factors at the individual, institutional, and country levels that influence students’ decision making, including students’ past experiences, funding, faculty members, and immigration policies. Moreover, it finds that the factors vary by students’ regions of origin and disciplines of study. Our findings, focused on international doctoral students in Canada, add to the ongoing conversation about  student mobility and add nuances on international students’ decision-making process in times of shifting landscape of higher education internationalization.